Climate‐vegetation interaction and amplification of Australian dust variability. Issue 22 (23rd November 2016) - Evans, Stuart; Ginoux, Paul; Malyshev, Sergey; Shevliakova, Elena
Abstract: Observations show that Australian dust activity varies by a factor of 4 on decadal timescales. General circulation models, however, typically fail to simulate this variability. Here we introduce a new dust parameterization into the NOAA/Geophysical Fluid Dynamics Laboratory climate model CM3 that represents land surface processes controlling dust sources including soil water and ice, snow cover, vegetation characteristics, and land type. In an additional novel step, we couple this new dust parameterization to the dynamic vegetation model LM3. In Australia, the new parameterization amplifies the magnitude and timescale of dust variability and better simulates the El Niño–Southern Oscillation‐dust relationship by more than doubling its strength. We attribute these improvements primarily to the slow response time of vegetation to precipitation anomalies and show that vegetation changes account for approximately 50% of enhanced dust emission during El Niño events. The amplified dust leads to radiative forcing over Australia greater than −1 and −20 W/m 2 at top of atmosphere and surface, respectively. Key Points: A new dust emission scheme that includes soil water and dynamic vegetation greatly increases long‐term variability of Australian dust Using the new parameterization CM3 gains the ability to simulate the observed ENSO‐dust relationship over Australia Increased dust variability has large impacts on the surface energy balance and possibly precipitation